An Analysis of ESP Students’ Reading Strategies: the Case of 3 rd Year LMD Nature and Life Sciences - CHENINI nacira (biblio centrale, université laghouat, 2012)
The current study investigates the reading strategies used by NLS students to solve the reading problems. It aims at analysing the most applied strategies to diagnose the language abilities and gaps. It is designed to get insights about NLS students’ reading abilities and difficulties. Such an analysis can explain the extent to which ESP apply reading strategies while reading specialised texts. The design of the current study is threefold. The first chapter deals with theoretical aspects related to ESP, reading, and reading strategies. The second chapter contextualise the research into its context. It explains the methodology and the research procedures used. Data are collected through teachers’ interview and students’ questionnaire. Findings and data analysis are presented in chapter three. The results are described and analysed qualitatively and quantitatively. NLS students apply reading strategies to solve the reading deficiencies. They rely mostly on content schema knowledge and translation in comparison with linguistic schema abilties. The use of reading strategies is determined specially by reading purposes and reading difficulties.